Peranan Masyarakat Adat Petalangan Dalam Mengamalkan Nilai Struktur Adat Berbasis Kearifan Lokal Lingkungan - Syafi’i, Muhammad (Dinamika Lingkungan Indonesia, 2018)
Indonesia's natural resources (SDA) along the equator, from the west to the east are experiencing accelerative, extensive and massive shrinkage. The erosion of natural resources almost does not put forward the concept of sustainable development, it has even entered the areas of indigenous peoples. The loss of land forests, for the people of Petalangan does not only mean losing livelihoods and livelihoods, but more fundamentally is the loss cultural resources. Petalangan Indigenous People in Riau were formerly in the government of the Kampar Kingdom then this kingdom changed its name to the Kingdom of Pelalawan. They live berpuak fathers and tribes. In adapting to the environment, community groups develop environmental wisdom as a result of the abstraction of experience managing the environment. This study aims to analyze the role of the indigenous people Petalangan in applying the values of customary structures based on environmental wisdom. The research method was conducted using qualitative descriptive method. Sources of data selected by purposive and snowball sampling. Data obtained data sourced from primary and secondary data. Data was collected through interviews and observations. From the research it can be concluded that kinship system, ethnic group, institutional structure, legal values, customary norms, sanctions and symbolics play a role in strengthening the local wisdom culture environment because they feel one lineage and in one community that has the same interests, the community feels land, river and the jungle must be guarded because of the common property in accordance with the sense of kinship possessed by the Petalangan community, in customary customs there is a regulation about the use that relates to the environment.